THE ANTIOXIDANT CAROTENOID CONSTITUENT FROM MARINE MACRO ALGAE - Ifah Munyah; Th. Dwi Suryaningrum; Heni Krisnawang (JOURNAL OF COASTAL DEVELOPMENT, 2006)
Most of the potentially harmful ejiects for the human body is hee radicals. A fee radical is any chemical species that has one or more unpaired electrons. Many fee radicals are unstable and highbz reactive. ~l-larmjtl %cts of jree radicals for the human body are their chemical reactivity can damage all types of cellular macromolecules and the chain qfects. Nutrition plays a key role in maintaining the body's enzymatic d%nses against fee radicals. It is believed to play an important role in cellular defenses against oxidative damage. Our work on new bioactive compounds hom marine macro algae has led to the isolation, characterization, and antioxidant assays of semi polar extract fom 5 d@rent macro algae (2 green algae and 3 brown algae) and structure elucidation. By using a in vitro antioxidant assays DPPH radical scavenging (I, I- dtphenyl-2·pici3¤llgzdrazy2D, the etil acetate extract of macro algae was separated by sephadex C-8 with eluent EtOAc/MeOH the faction analyzed through LCMS 20l0A.These studies of marine macro algae ojkred important new insight that the chlorophyll factions jiom brown algae have better inhibition activity against fee radicals than green algae did